2013
DOI: 10.1007/s11136-013-0497-3
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of quality of life in Spanish transsexuals attending a gender unit before genital sex reassignment surgery

Abstract: Cross-sex hormonal treatment, family support, and working or studying are linked to a better self-reported QoL in transsexuals. Healthcare providers should consider these factors when planning interventions to promote the health-related QoL of transsexuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
61
2
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(77 citation statements)
references
References 22 publications
7
61
2
7
Order By: Relevance
“…Several studies confirm a statistically significant improvement in self-reported quality of life (QoL) in both MTFs and FTMs receiving GAHT [42, 44, 53]. Hormonal intervention is also associated with higher levels of body satisfaction and self-esteem [44, 46•, 47], perhaps with a gender-specific effect.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies confirm a statistically significant improvement in self-reported quality of life (QoL) in both MTFs and FTMs receiving GAHT [42, 44, 53]. Hormonal intervention is also associated with higher levels of body satisfaction and self-esteem [44, 46•, 47], perhaps with a gender-specific effect.…”
Section: Resultsmentioning
confidence: 99%
“…There is little information about the main factors associated to a better sexual QoL. Previous studies on transsexuals analyzing QoL in different domains suggest a positive effect of hormone therapy [35–37]. Hurtado et al.…”
Section: Introductionmentioning
confidence: 99%
“…The results of previous cross-sectional studies suggest the positive effects of CSHT in FtM individuals [1214, 30, 34, 36]. However, a previous study using the MMPI did not show any significant difference [37].…”
Section: Discussionmentioning
confidence: 92%